A angústia filosófica de ser-outros: Fernando Pessoa e Heidegger no caminho da linguagem - Tanajura Júnior, José Mozart (Universidade do Vale do Rio dos Sinos, 2025)
Fernando Pessoa’s poetics open a path of possibilities for understanding the being and being-in-the-world of Dasein, from a perspective of dialogue between poetry and philosophy, based on Martin Heidegger’s hermeneutic ontology. In the unveiling of the phenomena present in Pessoa’s poetry, we inevitably encounter a peculiar aspect of his literary art: the creation of heteronyms. Through heteronymic creation, Pessoa investigates the meaning of his human-existence-in-the-world and frames his existential inquiries in an attempt to seek the deepest self through other selves present within him, expressed through various heteronyms. In his heteronymic proposal, Pessoa multiplies himself into other selves, becoming a poet within poets. Indeed, the process of heteronymy evokes in Pessoa a sense of anguish in the face of the existential crisis that arises at the core of the poet: being-others beyond literary creation. In this sense, our thesis posits that there is a configuration of selves in Pessoa that goes beyond a literary or aesthetic strategy in his poetic construction. Heteronymy is, in fact, an ontological condition of Fernando Pessoa in his self-understanding as Dasein, existing in the world with other beings and confronting the facticities imposed by existence. In this context, Heidegger’s philosophy helps us understand this ontological process in Pessoa, considering the themes of being, being-in-the-world, existence, anguish, and death present in the verses and vital context of the Portuguese poet. As Heidegger argues that in poetic language, being is unveiled and authentically revealed, Pessoa’s poetry effectively shows the unveiling of his own being through the verses of a heteronym, which, according to various literary critics, serves as a kind of self-portrait, even revealing ontological traits of the poet’s existence in the world. This heteronym is Álvaro de Campos, who, through his poetic proposal, exposes his existential crisis in an attempt to discover his true and profound self as heteronym and, consequently, as a reflection of Fernando Pessoa, his creator. This thesis affirms the viability of investigating the poet’s sense of being, through his existential anguish, by means of the open and creative dialogue between philosophy and poetry in the work of Fernando Pessoa, especially in the focus we made on the poetics of Álvaro de Campos, the heteronym who unveils the deep self of the poet, creator of other selves.
Keywords: Filosofia; Poesia; Martin Heidegger; Fernando Pessoa; Angústia; Heteronímia; Ontologia; Philosophy; Poetry; Anguish; Heteronymy; Ontology; ACCNPQ::Ciências Humanas::Filosofia